The South-Eastern Contact Area of Finnic Languages in the Light of Onomastics - Rahkonen, Pauli (2013)
The subject of the present dissertation is the West Uralic past, mainly linguistic and settlement history. It focuses on historically known ancient tribes and their linguistic backgrounds such as the Merya, Muroma, Me čera and Čude as well as on some unknown Uralic tribes and languages. The tools employed are onomastics (mostly hydronyms) and archaeology. The main results of the study are as follows. The Me čera seem to have been a tribe inhabiting the left bank of the Middle Oka and, surprisingly, they most probably spoke a Permian language. It seems that linguistically two kinds of Novgorodian Čudes lived in the catchment areas of the Upper Volkhov and Luga. Traces are found of East Čudes and, further west, West Čudes . Both of these were apparently not Finnic tribes. The language of the East Čudes shows similarities with Meryan. The West Čudian language shows some features of Mordvin and probably Early Proto-Finnic. The Meryans and Muromas were linguistically close relatives. Their languages may have been only two dialects of the same language. The Meryan language stretched as far as the western parts of Vologda oblast in the north. A kind of Meryan was spoken in the Moscow area as well. The Meryan language had a cognate language in the eastern parts of Novgorod and Tver oblasts which I have called East Čudian. Apparently another related language was spoken in the eastern parts of Leningrad oblast, in the south-western parts of Arkhangelsk oblast and in Karelia in the Lake Onega region probably before the Finnic era. Ancient Mordvin-type toponyms are found in Kaluga and Moscow oblasts. There seem to have been two extreme edges of ancient Mordvin hydronyms, the first in the environs of the town of Tver and another on the left bank of the Volga between the river Kostroma and the estuary of the Un a. It is possible that an unknown Uralic x-language (or languages) was spoken in Finland, Karelia and in the North Russian lakeland. In my opinion, this language probably cannot be derived from Proto-Finnic or ...